Protein carbamylation and chronic kidney disease progression in the Chronic Renal Insufficiency Cohort Study. Issue 1 (2nd December 2020) - Kalim, Sahir; Berg, Anders H; Karumanchi, Subbian Ananth; Thadhani, Ravi; Allegretti, Andrew S; Nigwekar, Sagar; Zhao, Sophia; Srivastava, Anand; Raj, Dominic; Deo, Rajat; Frydrych, Anne; Chen, Jing; et al.
Abstract: Background: Protein carbamylation is a post-translational protein modification caused, in part, by exposure to urea's dissociation product cyanate. Carbamylation is linked to cardiovascular outcomes and mortality in dialysis-dependent end-stage kidney disease (ESKD), but its effects in earlier pre-dialysis stages of chronic kidney disease (CKD) are not established. Methods: We conducted two nested case–control studies within the Chronic Renal Insufficiency Cohort Study. First, we matched 75 cases demonstrating CKD progression [50% estimated glomerular filtration rate (eGFR) reduction or reaching ESKD] to 75 controls (matched on baseline eGFR, 24-h proteinuria, age, sex and race). In the second study, we similarly matched 75 subjects who died during follow-up (cases) to 75 surviving controls. Baseline carbamylated albumin levels (C-Alb, a validated carbamylation assay) were compared between cases and controls in each study. Results: At baseline, in the CKD progression study, other than blood urea nitrogen (BUN) and smoking status, there were no significant differences in any matched or other parameter. In the mortality group, the only baseline difference was smoking status. Adjusting for baseline differences, the top tertile of C-Alb was associated with an increased risk of CKD progression [odds ratio (OR) = 7.9; 95% confidence interval (CI) 1.9–32.8; P = 0.004] and mortality (OR = 3.4; 95% CI 1.0–11.4; P = 0.05) when compared with the bottom tertile. C-Alb correlated with eGFR but was more strongly correlated with BUN. Conclusions: Our data suggest that protein carbamylation is a predictor of CKD progression, beyond traditional risks including eGFR and proteinuria. Carbamylation's association with mortality was smaller in this limited sample size. Graphical Abstract: